Dukungan keluarga dan kualitas hidup bagi penderita stroke pada fase pasca akut di Kabupaten Wonogiri - Rahman Rahman; Fatwa Sari Tetra Dewi; Ismail Setyopranoto (Fakultas Kedokteran Universitas Gadjah Mada, 2017)
Family support and quality of life for stroke patients in the post-acute phase of WonogiriPurposeThis research aimed to determine the relationship of family support such as emotional, information, instrumental and reward with the quality of stroke patients in the post-acute phase in Wonogiri.MethodsA cross-sectional study was conducted involving interviews and the use of medical record data of 161 post-acute stroke patients in Wonogiri.ResultsThis study showed that there was a significant correlation of information support (p= 0.000), and awareness support (p=0.000) with the quality of life of post-acute stroke patients. ConclusionThe study confirms the importance of family support in terms of information support and awards support to the quality of life of patients with post-acute stroke.